2007
DOI: 10.1021/jp065428k
|View full text |Cite
|
Sign up to set email alerts
|

Physisorption Kinetics in Carbon Nanotube Bundles

Abstract: The kinetics of gas uptake on different regions of carbon nanotube bundles is investigated by means of a kinetic Monte Carlo scheme. A lattice-gas description is used to model the adsorption of particles on a onedimensional chain of sites under two types of dynamics: (a) external kinetics, in which the chain is on the bundle's external surface directly exposed to the gas, and (b) pore-like kinetics, expected to occur inside the tubes and interstitial channels, where adsorption occurs via gas diffusion from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
98
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(105 citation statements)
references
References 39 publications
6
98
1
Order By: Relevance
“…The theoretical studies have also found that a completely different mechanism for reaching equilibrium exists for nanotubes that have open ends. 13 In previous publications, in which we studied gas adsorption kinetics on closed-and openended nanotubes, we determined experimentally that these predictions were correct. 4,5 Here we explore the dependence of the equilibration time on the length of the adsorbed molecule, and, for each adsorbate, we also explore the dependence of the equilibration time on fractional coverage.…”
Section: Introductionmentioning
confidence: 80%
“…The theoretical studies have also found that a completely different mechanism for reaching equilibrium exists for nanotubes that have open ends. 13 In previous publications, in which we studied gas adsorption kinetics on closed-and openended nanotubes, we determined experimentally that these predictions were correct. 4,5 Here we explore the dependence of the equilibration time on the length of the adsorbed molecule, and, for each adsorbate, we also explore the dependence of the equilibration time on fractional coverage.…”
Section: Introductionmentioning
confidence: 80%
“…It is interesting to note that the adsorption reaches equilibrium much faster on external sites (grooves and outer surfaces) than on the internal sites (interstitial channels and inside the tube) under the same pressure and temperature conditions. The external sites are directly exposed to the adsorbing material; the adsorption process on internal sites has to be initiated on the ends of the pore, followed by diffusion to the sites at the interior [49,50]. Second, the fraction of opened and unblocked nanotubes can greatly influence the overall adsorption capacity.…”
Section: Adsorption Properties Of Cntsmentioning
confidence: 99%
“…It is interesting to note that recent theoretical calculations by Calbi et al, have predicted a two orders of magnitude longer adsorption time of gases to IC sites compared to OG sites. 50 Their prediction was confirmed by experimental adsorption studies of Ar on open-ended SWNT bundles by Migone et al, 51 To do a quantitative analysis of the data, we tried applying a random-walk diffusion model 52 to our data. According to this model, an initial packet of particles would diffuse out over time (t) through collisions with the environment similarly to a random-walk process, and this packet's mean-square displacement would be described as (in one dimension) where x 2 is the mean-square displacement and D is the diffusion coefficient.…”
Section: A 4 He Binding Energies On Single-wall Carbon Nanotube Bundmentioning
confidence: 55%
“…14 Also, Calbi et al, have predicted much slower adsorption of gases to IC sites due to diffusive adsorption process. 50 So we interpret the y intercept value as the number of atoms adsorbed onto OG site. 55 Using some further assumptions [the mean-square displacement divided by the adsorbate distance is the number of adsorbates in the diffusion channel (IC sites)], we obtained the diffusion coefficient from the slope as well.…”
Section: A 4 He Binding Energies On Single-wall Carbon Nanotube Bundmentioning
confidence: 99%